Bisdemethoxycurcumin and Its Cyclized Pyrazole Analogue Differentially Disrupt Lipopolysaccharide Signalling in Human Monocyte-Derived Macrophages. (8th February 2018) - Tedesco, Serena; Zusso, Morena; Facci, Laura; Trenti, Annalisa; Boscaro, Carlotta; Belluti, Federica; Fadini, Gian Paolo; Skaper, Stephen D.; Giusti, Pietro; Bolego, Chiara; Cignarella, Andrea
Abstract : Several studies suggest that curcumin and related compounds possess antioxidant and anti-inflammatory properties including modulation of lipopolysaccharide- (LPS-) mediated signalling in macrophage cell models. We here investigated the effects of curcumin and the two structurally unrelated analogues GG6 and GG9 in primary human blood-derived macrophages as well as the signalling pathways involved. Macrophages differentiated from peripheral blood monocytes for 7 days were activated with LPS or selective Toll-like receptor agonists for 24 h. The effects of test compounds on cytokine production and immunophenotypes evaluated as CD80 + /CCR2 + and CD206 + /CD163 + subsets were examined by ELISA and flow cytometry. Signalling pathways were probed by Western blot. Curcumin (2.5–10 μ M) failed to suppress LPS-induced inflammatory responses. While GG6 reduced LPS-induced I κ B- α degradation and showed a trend towards reduced interleukin-1 β release, GG9 prevented the increase in proinflammatory CD80 + macrophage subset, downregulation of the anti-inflammatory CD206 + /CD163 + subset, increase in p38 phosphorylation, and increase in cell-bound and secreted interleukin-1 β stimulated by LPS, at least in part through signalling pathways not involving Toll-like receptor 4 and nuclear factor- κ B. Thus, the curcumin analogue GG9 attenuated the LPS-induced inflammatory response in human blood-derived macrophages and may therefore represent an attractive chemical template for macrophage pharmacological targeting.